Conjugated linoleic acid in meat and milk from ruminants: genetic and dietary sources of variation - Secchiari, P.; Mele, M.; Serra, A. (Progress in Nutrition, 2007)
The conjugated linoleic acid (CLA) isomers refer to a group of fatty acids contained in milk and meat from ruminants. Numerous physiological properties have been attributed to CLA including action as an antiadipogenic, antidiabetogenic, anticarcinogenic and antiatheroscletotic agent. In light of the potential benefits to long-term human health, there is considerable interest in developing strategies to enhance CLA content in food. The milk and meat content from ruminants is highly variable and several dietary and genetic factors concur to affect it. Several investigation have highlighted that some diet characteristics (polyunsaturated fatty acid content, forage:concentrate ratio; charbohydrate:protein ratio; type of the forage) are able to significantly affect the CLA synthesis. Concerning the genetic sources of variation, a few knowledges are available. Some investigation highlighted a wide variability in the milk CLA content, when animals are fed with the same dietary regimen. This finding has been proposed to be related to a potential genetic variability. A putative role may be played by the genetic polymorphism of D9 desaturase gene. This gene encodes for the homonymous enzyme that is responsible of the endogenous synthesis of the main CLA isomer in milk and meat: the cis-9, trans-11, also namely rumenic acid.